PERAN KUALITAS PRODUK, CITRA MEREK DAN INOVASI PRODUK DALAM KEPUTUSAN PEMBELIAN BARANG MEWAH: STUDI PADA PENGGUNA I-PHONE DI KOTA TANGERANG - Sutisna, Sutisna; Herawati, Upi; Bahits, Abdul (Bussman Journal : Indonesian Journal of Business and Management, 2024)
One of the most important efforts of marketers is how to drive consumer purchasing decisions. Many variables affect purchasing decisions, including product quality, brand image, and product innovation. This study aims to reveal the role of these three variables in the decision to purchase luxury goods. This study is a quantitative study involving 96 respondents who have bought and used iPhones in the Tangerang city area. The sampling technique used is purposive sampling and uses multiple regression statistical methods to analyze the data. The results of the study show that product quality affects the purchase decision, brand image affects the purchase decision of luxury goods, but product innovation does not affect the purchase decision of luxury goods. The study also found that the brand image perceived by users had a stronger influence on the purchase decision of luxury goods compared to the product quality variable